US Dermatology Resident Responses about the COVID-19 Pandemic: Results from a Nationwide Survey. Issue 9 (September 2020) - Li, Yumeng M.; Galimberti, Fabrizio; Abrouk, Michael; Kirsner, Robert S.
Abstract : Objectives: The coronavirus disease 2019 (COVID-19) pandemic has drastically changed resident training in the United States. Here, we explore the early perceived effects of COVID-19 on dermatology residents through an electronic sample survey and identify possible areas for targeted improvement in lieu of a possible second wave of COVID-19 cases. Methods: On April 3, 2020, a survey of link with 25 questions was sent to dermatology program coordinators to be disseminated among dermatology residents in the United States. The survey was closed on April 13, 2020. All of the questions were optional and no personal identifiers were collected. Results: A total of 140 dermatology residents from 50 different residency programs across 26 states responded to the survey. The majority of respondents (85%) reported negative effects of COVID-19 on their overall wellness. Despite the majority of residents (92%) speculating that COVID-19 will have negative long-term effects on the US economy, only 33% agreed or strongly agreed that it will affect their job prospects. Teledermatology was widely implemented following the declaration of a national emergency (96% of represented residencies compared with only 30% before the pandemic), with heavy resident involvement. The majority of residents (99%) reported having virtual didactics and that they found them to be beneficial. Most residents were uncomfortable with the prospect of being reassigned to a nondermatology specialty during the pandemic. In addition, 22% of residents believed that their leadership were not transparent and prompt in addressing changes relating to COVID-19. Conclusions: Dermatology residents were affected negatively by COVID-19 in regard to their well-being, clinical training, and education. Several areas of improvement were identified that could improve our preparedness for a second wave of the virus. Abstract : The COVID-19 pandemic has changed, at least temporarily, the face of medicine. Residency training across the United States in all specialties has undergone significant changes. This is particularly true for dermatology, a mostly outpatient specialty with a high emphasis on visual examinations and in-office procedures. This article provides an early insight into how dermatology residents across the nation are coping with these changes and gives these young physicians an opportunity to speak of their experiences.Supplemental digital content is available in the text.